2019
DOI: 10.1029/2019tc005580
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on Trenchward Arc Migration and Backarc Magmatism in the North Patagonian Andes in the Context of Nazca Plate Rollback

Abstract: Geochemical and geochronological data reveal that late Oligocene‐early Miocene time is a break point in the evolution of Andean magmatism. The Patagonian Andes registered the onset of arc volcanism since the late Eocene forming part of the El Maitén Belt, whose development was driven by the subduction of the Farallon/Nazca plates beneath the Andean margin. During the Oligocene, the El Maitén Belt shows a change in the geochemical signature of its magmas from tholeiitic to calc‐alkaline compositions, reflecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 119 publications
(294 reference statements)
0
23
0
Order By: Relevance
“…2) marked by the Lower Jurassic Subcordillera Plutonic Belt (Gordon and Ort, 1993;Page and Page, 1999) and by the Upper Jurassic-Lower Cretaceous North Patagonian Batholith (Suárez and De la Cruz, 2001;Pankhurst et al, 2003). Indeed, lateral shifts of the magmatic arc either toward the trench or toward the eastern foreland are promoted by variations of the subduction zone configuration involving slab steepening or shallowing episodes, respectively (e.g., Coira et al, 1993;England et al, 2004;Kay et al, 2005;Ramos and Folguera, 2005;Syracuse and Abers, 2006;Folguera and Ramos, 2011;Spagnuolo et al, 2012;Schellart, 2017;Fernández Paz et al, 2019). Coeval volcanism is recorded by the Middle-Upper Jurassic Lago La Plata Formation (correlated with the Ibáñez Group in Chile; Folguera and Iannizzotto, 2004;Olivero, 1982) and the Lower Cretaceous Divisadero Group (Ramos, 1981;Suárez et al, 2009).…”
Section: Geological Settingmentioning
confidence: 99%
“…2) marked by the Lower Jurassic Subcordillera Plutonic Belt (Gordon and Ort, 1993;Page and Page, 1999) and by the Upper Jurassic-Lower Cretaceous North Patagonian Batholith (Suárez and De la Cruz, 2001;Pankhurst et al, 2003). Indeed, lateral shifts of the magmatic arc either toward the trench or toward the eastern foreland are promoted by variations of the subduction zone configuration involving slab steepening or shallowing episodes, respectively (e.g., Coira et al, 1993;England et al, 2004;Kay et al, 2005;Ramos and Folguera, 2005;Syracuse and Abers, 2006;Folguera and Ramos, 2011;Spagnuolo et al, 2012;Schellart, 2017;Fernández Paz et al, 2019). Coeval volcanism is recorded by the Middle-Upper Jurassic Lago La Plata Formation (correlated with the Ibáñez Group in Chile; Folguera and Iannizzotto, 2004;Olivero, 1982) and the Lower Cretaceous Divisadero Group (Ramos, 1981;Suárez et al, 2009).…”
Section: Geological Settingmentioning
confidence: 99%
“…Paleogene extension of Iran is likely to have been related to subduction of old oceanic lithosphere, which favors roll-back. Furthermore, the interaction between the subducting lithosphere and the mantle transition zone for the old Tethyan slab could have increased the slab-pull forces, which triggered slab steepening and accelerated roll-back, as was proposed for magmatic flare-up in the Patagonian Andes (e.g., Iannelli et al, 2018;Paz et al, 2019).…”
Section: Change In Subduction Anglementioning
confidence: 99%
“…This magmatic lull was accompanied with ophiolite exhumation and erosion in Iran MF and BA. Recent syntheses for arcs worldwide including the Andes, suggest that after ridge or seamount subduction a period of slow subduction with lull magmatism occurs until the slab-pull forces restored (e.g., Iannelli et al, 2018;Paz et al, 2019). The magmatic lull at 35-20 Ma (and even 15-10 Ma) is probably related to the onset of continental collision between Iran and Arabia followed by slab detachment in Miocene.…”
Section: 1029/2019jb018460mentioning
confidence: 99%
“…1 y 2). The greatest extension is recorded in the Traiguén Formation (Espinoza and Fuenzalida, 1971), in which deep-marine turbidite deposits (Encinas et al, 2016a) are found overlying or associated with supra-subduction zone pillow lavas overprinted by ocean-floor metamorphism (Hervé et al, 1995). In some localities, the volcano-sedimentary units are profusely intruded by mafic dykes (Silva et al, 2003), resembling the emplacement of a dyke swarm on a thin and attenuated ocean-like crust.…”
Section: Introductionmentioning
confidence: 99%